Under roof natures. Brazil, Mexico and Venezuela’s pavilions at Brussels 1958 - Alayón González, José Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
The purpose of this paper is to analyse the relationships between nature, identity and architecture through the pavilions of three countries, great exponents of Latin American modern movement at a key time of international political tension, renewed technological optimism and local revisions of architectural modernity. The aim is to establish its position against nature imaginaries, through the comparison of institutional, curatorial and architectural discourses, in an event dedicated to a new humanism under atomic energy power that was inspiring and threatening at the same time. The result of this research is the demonstration of the tension between the foundational myth of the ungraspable territorial, the need for the abstraction of the new architecture and the economical exploitation. This article documents and illustrates the nature presented and represented in the architecture and the objects exhibited under the three Latin American roofs, sometimes in clear contradiction — idealized and exploited nature for the construction of the imaginary of the young nations.
Keywords: Expo '58; Exhibition pavillions; Nature imaginaries; Latin-American modern architecture; Modern gardens